Calidad del cuidado de enfermería y nivel de depresión del adulto mayor hospitalizado - Armas Monzon, Fanny Madiley (2016)
This research study, cross correlacional- descriptive, was conducted during the months of July 2015 to January 2016, in the Leoncio Prado Hospital of Huamachuco; in order to determine the relationship between the quality of nursing care and the level of depression in the elderly hospitalized. The sample universe consisted of 40 older adult patients selected according to the inclusion criteria. Two instruments were used for data collection: scale on the quality of nursing care developed based on 9 of the 10 factors care nursing practice proposed by (Waldow, 1998), Geriatric Depression Scale Yesavage created by Yesavage in 1986. The analysis of the relationship between the study variables was performed by test chi square independence criteria. The results are presented in leaderboards single and double entry number / percentage frequencies as well as statistical graphs. After the analysis has led to the following conclusions. That the highest percentage 60% of hospitalized patients indicates the quality of care as poor, 22% good, and 18% regularly. Observed that most hospitalized patients 80% have a moderate level of depression, 15% have a level of severe depression, 5% a level of mild depression and 0% no depression. According to statistics chi square test shows that there is no relationship between variables. (P = 0.148).